Adams and Victor's principles of neurology - Ropper, Allan H.; Klein, Joshua; Samuels, Martin A. (New York : McGraw Hill, 2023)
This edition focuses on the wise application of science, evidence from trials, and is closely coupled to the traditional value of the neurological history and examination-essentially the craft of neurology--
Includes bibliographical references and index.
Keywords: Nervous System Diseases; Neurologic Manifestations